MENGGALAKKAN KEPARIWISATAAN KABUPATEN BIMA DENGAN KONSEP PENYEBARAN INFORMASI WISATA MENGGUNAKAN MODERNISASI WEBSITE - Layati Layati; Joko Aryanto (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Bima Regency has a lot of tourist attractions, but there are still many people who do not know about them, including the people of Bima itself and also from outside the region, because of the difficulty of getting information about tourist attractions in Bima Regency. This research aims to create a web-based Bima Regency tourism information system that can introduce various tourist attractions to the wider community in order to improve the performance of tourism marketing in Bima Regency. This tourism information system was built using the PHP programming language and MySQL as the database. The system development method used is waterfall, which consists of the stages of needs analysis, system design, coding, testing, and maintenance. The tourist data displayed includes descriptions of attractions, locations, accessibility, facilities, costs, and documentation in the form of photos. The result of the research is an information system that can help make it easier for tourists to get information about tours in Bima district, and this website makes it easier for tourists from outside the area to book tour packages and hotel reservations.